STRATEGIES OF SOCIAL REPRODUCTION OF FAMILY FARMERS OF THE RURAL COMMUNITIES OF CATALAO (GO) - Silva, Juniele Martins [UNESP]; Medeiros Hespanhol, Rosangela Aparecida de [UNESP] (Univ Estado Rio Janeiro, 2016)
The rural areas in Brazil have undergone sweeping changes from mainly the 1970s, in response to the agricultural modernization process. This occurred unequally, favoring products for export, the South, Southeast and, subsequently, Midwest of Brazil and the large and medium farmers. In this context, the smallholder farmers were excluded of modernizing process, having employed various strategies which allow their social reproduction. With de purpose to understand the main characteristics of family farming, giving emphasis to undertaken social reproduction strategies, this paper is proposed. Empirically, there was focus to family farmers in rural communities Custodia, Ribeirao, Sao Domingos and Tambioco in the municipality of Catalao (GO). For the development of this study, there have been literature review; desk research and empirical research in rural communities Custodia (inhabited by 54 families), Ribeirao (60 families), Sao Domingos (51 families) and Tambioco (51 families), being applied, respectively, 19 (35.18%), 21 (35.00%), 17 (33.33%) and 18 (35.29%) interview forms with family farmers residing in these localities.
Keywords: Family farming; Strategies of social reproduction; Place; Rural communities; Municipality of Catalao (GO)